Trinidad and Tobago - (:unkn) unknown (Norman Parkinson, 2011)
Description printed on the back of the postcard: "Seen through the coconut palms, Pigeon Point, Tobago, where the warm sea always welcomes you."
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Beaches; Beachgoers; Boats and boating